Intrauterine growth restriction and its associated factors in Tehran, comparing 3 common standards - Mahtab Toulany; Narjes Khalili; Mohammad Heidarzadeh; Abbas Habibelahi; Arghavan Haj-sheykholeslami (PLoS ONE, 2025)
Objectives Several standard charts have been proposed for the diagnosis of intrauterine growth restriction (IUGR) at birth but no global or national consensus exists on using any of them. We aimed to evaluate and compare the prevalence of IUGR in Tehran using 3 common standards and identify the associated factors. Methods Using the Iranian Maternal and Neonatal Network registry, we extracted the data of all singleton live births in Tehran province of Iran in 2018 to eliminate the possible confounding effects of the COVID-19 pandemic. We defined IUGR as having a birth weight less than the 10th percentile for gestational age using 3 standards including World Health Organization’s and INTERGROWTH-21st charts and the same population’s 10th percentiles. Logistic regression was used to identify the associated factors. Results There were 187031 singleton live births. The prevalence of IUGR using WHO, INTERGROWTH-21st, and the population’s 10th percentile was 11.8, 4.2, and 9.7 percent respectively; Among these, 7681 cases (4.1%) were identified by all 3. Neonatal trisomy 21, maternal addiction, eclampsia/pre-eclampsia, chronic hypertension, history of abortion, Primigravidity, being older than 35 yrs. and parental consanguinity were positively associated with IUGR where mother’s gestational diabetes, higher education level, delivering the baby in a private hospital and living in Paakdasht or Shahryar cities were inversely associated with IUGR. Conclusion The IUGR prevalence highly depended on the standards used ranging from 4.2 to 11.8%, showing a great need for a global consensus. Neonatal trisomy 21, maternal addiction and eclampsia/pre-eclampsia had the strongest positive associations with IUGR.